ANALISIS TINGKAT KEPUASAN WISATAWAN PADA DESTINASI PARIWISATA KOTA LHOKSEUMAWE - Agustinawati Agustinawati; Samsidar Samsidar (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
Tourist satisfaction is an important indicator that must be considered in the service business sector, especially businesses in tourism destinations. It is a standard that can be used to evaluate the level of performance of tourism services and products. Lhokseumawe City has several tourism destinations that are in great demand and become tourist destinations for local and foreign tourists. This study aims to describe the level of tourist satisfaction based on indicators of product, price, promotion, location, people, process and physical evidence. Data collection was carried out using questionnaires which were distributed directly to tourists visiting tourist destinations using accidental sampling and analyzed using the tendency category method, namely high, medium and low. The results of the study indicate that the level of tourist satisfaction with tourism destinations in the city of Lhokseumawe as a whole belongs to the medium category